Evaluasi Penerapan SAK ETAP pada Koperasi Karyawan “Respati’ Universitas Respati Yogyakarta - Andre Kussuma Adiputra; Sri Muntari; Poly Endrayanto Eko Christmawan (LPPM University 17 Agustus 1945 Samarinda, 2023)
This research was conducted to find out how measurement, recognition, presentation, and disclosure of report elements in financial reporting of cooperatives based on financial accounting standards of entities without public accountability in the